Survey of Knowledge, Attitude and Performance of Tehran Metro Service Workers towards COVID Prevention - zahrasadat MOSAVIFARD; Farahnaz KHAJEHNASIRI (Shahid Sadoughi University of Medical Sciences, 2021)
introduction: Coronavirus (COVID-19) has recently emerged as a global threat. Workers' knowledge, attitudes, and practices about this new infectious disease are crucial to its prevention and control. This study was conducted to the status of knowledge, attitude, and practice was determined according to the COVID-19 prevention guidelines and the factors affecting it in the service workers of Tehran Metro Line 1 in the fall of 2020 Methods: This cross-sectional (descriptive-analytical) study was performed on 113 service-cleaning workers of Tehran Metro Line 1 with a mean and standard deviation of the age of 35.38+_5.43 in the fall of 2020. Data collection tools included a demographic questionnaire and a 32-item questionnaire to assess the status of knowledge, attitude, and practice to the COVID-19 prevention guidelines (with optimal validity and reliability). Answers were measured with pros, cons, no comments. Findings were presented by descriptive and analytical statistics and data analysis was performed by analytical tests of SPSS software version 25 with a significance level of p <0.05. Results: The results of the study showed that in the field of knowledge, attitude, and practice with 74.9%, 83.2%, and 99.2% of the participants were at a good level, respectively. There was a significant relationship between age and attitude of participants in the study (p <0.05) so that the The attitudes of 30-34 years old were significantly different from the attitudes of other age groups There was also a significant positive relationship between education and performance of participants (p <0.05), people with a bachelor's degree had better performance. The relative frequency of non-COVID-19 infection in the study participants from the beginning of the disease until now (autumn 1399) was 68.1%. Conclusion: In order to correct misconceptions and promote awareness and attitudes of the population of the study about COVID-19 , it is recommended that education and information be provided through the media. The good level of knowledge, attitude, and practice of the service workers - cleaning the subway towards the Covid-19 virus, had caused the incidence of coronary heart disease among them to be almost 30%. In this regard, the distribution of appropriate personal protective equipment, daily disinfection of subway stations can be effective factors in reducing the incidence of workers.